13 uždavinys

12 uždavinys14 uždavinys

f(x) =. Apskaičiuokite f'(√2)

Sprendimas.

 ( saknis(2)* x^2+saknis(2))  = 
 ( saknis(2)* x^2+saknis(2)) =  = 
=
Paaiškinimas:
Sumos išvestinė (f+g)′ = f′ + g′
 ( saknis(2)* x^2)+ saknis(2) =  = 
= 0
Paaiškinimas:
Konstantos išvestinė yra 0
 ( saknis(2)* x^2)+0 =  = 
 ( saknis(2)* x^2) =  = 
=
Paaiškinimas:
iškeltas prieš skliaustus
 saknis(2)* ( x^2) =  = 
=
Paaiškinimas:
Laipsnio išvestinė, kur n = 2
 saknis(2)* 2* x =  = 
Paaiškinimas:
Keitimas = .
 saknis(2)* 2* saknis(2) =  = 
 saknis(2)* saknis(2)* 2 =  = 
=
 2* 2 =  = 
=
4
 = 
 = 
 = 
 = 
 = 

Atsakymas: 4

12 uždavinys14 uždavinys